Relation Between Reading and Quality of Life of Adolescents: Results of Cohort Cross-Sectional Sequential Study - Elena G. Vikhareva; Irina V. Vinarsky; Maya A. Khan; Tatyana V. Tretyakova; Vladislav V. Chernikov ("Paediatrician" Publishers LLC, 2016)
Background: Determination and monitoring of the quality of life of adolescents are needed to examine the social conditions of their life.Objective: Our aim was to study the relation between reading books and the number of read books with the quality of life of adolescents. Patients and Methods: We conducted a cross-sectional cohort study where examined the quality of life of children aged 13-18 years attending secondary educational institutions of Izhevsk city and Udmurtia rural districts. Using PedsQL questionnaire, we analyzed the physical, emotional and social component of the quality of life of adolescents, school functioning and overall assessment score of the quality of life. The attitude to reading was determined by the results of the answers to questions about the love of reading (yes/no) and the number of read books.Results: The study included 2,947 high school students, in which 2,473 (83.9%) adolescents indicated their attitude toward reading. It has been shown that students who enjoy reading (42.2%) have a lower assessment score of the quality of life on the scale of «emotional functioning» (66 ± 17) and higher - on the scale of «school functioning» (69 ± 15) than their peers not liking to read (68 ± 16 and 66 ± 15, respectively; p < 0.001). The number of read books was associated with the quality of life assessment on the scale of «physical functioning» and «school functioning» as well as with the assessment of the social component of quality of life for girls.Conclusion: The studied factors («reading books» and «the number of read books») are related to the quality of life of adolescents that may be taken into account in the preparation of educational programs.